Diseño de un plan de marketing para la Fundación para el desarrollo del menor con necesidades especiales como generador de recursos para la acción social - Narváez Correa, Ana Silvia (2015)
This paper deals with the implementation of a marketing plan to the Foundation for the development of children with special needs "FUDEMNES" institution that began its work in June 2003 with the intention of providing rehabilitation services to children and youth in need specials Quito. Examining the low economic and social development presents FUDEMNES, we have seen the need to contribute to the development of a marketing plan to increase sales of the foundation, because today has a small number of users and it does not allow them to improve the current conditions of its offer. In this research concepts of several renowned authors who have been a great contribution to marketing are defined, the macro environment of the foundation with the help of the competitive forces of Porter and the microenvironment through political, economic, social, technological analysis is analyzed, demographic and motivational analyzes customer profile, key competitors of the foundation, and also several strategies and development-oriented activities of the foundation are raised. The purpose of the research project is to find a social and economic benefit for the foundation, through better market position and better service delivery, so that FUDEMNES invest in improvements to the development of their social offer, including helping children with special needs of low income.